Shakespeare's Hamlet - Shakespeare, William, 1564-1616; Taylor, George Coffin, 1877-1961; Smith, Reed (Boston : Ginn and Company, 1964)
William Shakespeare's "Hamlet," in a translation by Robert Panara and Leonard Siger, presented by the Gallaudet College Dramatics Club, director George Detmold, stage manager Gilbert Eastman, business manager Ronald Sutcliffe, publicity manager Agnes Dunn, costumes by Edith Hill, reader Leonard Siger.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: SHAKESPEARE, WILLIAM, -- 1564-1616 -- TEATRO; TEATRO INGLES; HAMLET (PERSONAJE FICTICIO) -- DRAMA